Pembuatan Biodiesel dengan Cara Adsorpsi dan Transesterifikasi Dari Minyak Goreng Bekas - Lisa Adhani; Isalmi Aziz; Siti Nurbayti; Christie Adi Octavia (Syarif Hidayatullah State Islamic University, 2016)
Used cooking oil can be used as raw material for biodiesel, but the levels of free fatty acids (Free Fatty Acid, FFA) is quite high. It is necessary for pretreatment in the form of the adsorption process to reduce levels of FFA. This study aims to determine the optimal conditions of adsorption process and determine the quality of biodiesel produced from adsorption processes and transesterification. Natural zeolites are used as adsorbents activated beforehand using ammonium chloride, calcined and heated to obtain H-zeolite. Furthermore, the adsorption process optimization includes the time, the adsorbent concentration, temperature and particle size. The oil that is already in the adsorption catalyst is reacted with methanol and KOH to obtain biodiesel. The optimum adsorption conditions obtained at the time of 90 minutes, the concentration of H-zeolite 12%, temperature 90 ° C, and a particle size of 0.2 mm that can lower FFA levels from 3.2% to 1.1%. Biodiesel produced meets the quality requirements of SNI 04-7182-2006 with a water content of 0.02%, a density of 857.60 kg / m3, the acid value of 0.29 mg-KOH / g, iodine number 15.71, saponification 168 , 02 and cetane index of 75.62. Compounds contained in biodiesel are methyl 9-octadecanoic (49.45%), methyl heksadekanoat (20.79%), and methyl 9,12oktaekanoat 9.12 (18.87%). Keywords: Biodiesel, used cooking oil, adsorption, transesterification, H-zeolitDOI: http://dx.doi.org/10.15408/jkv.v2i1.3107